Genome-wide identification of MAPK family in papaya (Carica papaya) and their involvement in fruit postharvest ripening - Shengnan Zhu; Yuxing Mo; Yuyao Yang; Shiqi Liang; Shuqi Xian; Zixin Deng; Miaoyu Zhao; Shuyi Liu; Kaidong Liu (BMC Plant Biology, 2024)
Abstract Background Papaya (Carica papaya) is an economically important fruit cultivated in the tropical and subtropical regions of China. However, the rapid softening rate after postharvest leads to a short shelf-life and considerable economic losses. Accordingly, understanding the mechanisms underlying fruit postharvest softening will be a reasonable way to maintain fruit quality and extend its shelf-life. Results Mitogen-activated protein kinases (MAPKs) are conserved and play essential roles in response to biotic and abiotic stresses. However, the MAPK family remain poorly studied in papaya. Here, a total of nine putative CpMAPK members were identified within papaya genome, and a comprehensive genome-wide characterization of the CpMAPKs was performed, including evolutionary relationships, conserved domains, gene structures, chromosomal locations, cis-regulatory elements and expression profiles in response to phytohormone and antioxidant organic compound treatments during fruit postharvest ripening. Our findings showed that nearly all CpMAPKs harbored the conserved P-loop, C-loop and activation loop domains. Phylogenetic analysis showed that CpMAPK members could be categorized into four groups (A-D), with the members within the same groups displaying high similarity in protein domains and intron–exon organizations. Moreover, a number of cis-acting elements related to hormone signaling, circadian rhythm, or low-temperature stresses were identified in the promoters of CpMAPKs. Notably, gene expression profiles demonstrated that CpMAPKs exhibited various responses to 2-chloroethylphosphonic acid (ethephon), 1-methylcyclopropene (1-MCP) and the combined ascorbic acid (AsA) and chitosan (CTS) treatments during papaya postharvest ripening. Among them, both CpMAPK9 and CpMAPK20 displayed significant induction in papaya flesh by ethephon treatment, and were pronounced inhibition after AsA and CTS treatments at 16 d compared to those of natural ripening control, suggesting that they potentially involve in fruit postharvest ripening through ethylene signaling pathway or modulating cell wall metabolism. Conclusion This study will provide some valuable insights into future functional characterization of CpMAPKs, and hold great potential for further understanding the molecular mechanisms underlying papaya fruit postharvest ripening.